1968
DOI: 10.1177/003754976801000506
|View full text |Cite
|
Sign up to set email alerts
|

A new high performance computer d-c amplifier

Abstract: A new computer d-c amplifier designed for very fast as well as for real-time analog/hybrid computation combines large bandwidth (30 MHz gain-bandwidth product) and high mid-band gain (68 dB at 10 KHz) with full ± 10V, 30mA output to 5.0 MHz, and low open-loop output im pedance (50 ohms at 10 KHz). High d-c gain (120 dB) and exceptionally low drift (50 pA/°C, 2.5 μV/°C ) is obtained with the aid of an inexpensive hot-substrate integrated- circuit preamplifier rather than with conventional chopper stabilization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The "run number" is used as a blocking factor to reduce the variation associated with various job streams. Naylor et al (1967) recommend using this approach to eliminate the effect of dependencies between cells when using common random numbers -thus making an ANOVA appropriate. A similar approach has also been used by Ragatz and Mabert (1988), who employed Job Set as a dummy variable in their ANOVA.…”
Section: $ Resultsmentioning
confidence: 99%
“…The "run number" is used as a blocking factor to reduce the variation associated with various job streams. Naylor et al (1967) recommend using this approach to eliminate the effect of dependencies between cells when using common random numbers -thus making an ANOVA appropriate. A similar approach has also been used by Ragatz and Mabert (1988), who employed Job Set as a dummy variable in their ANOVA.…”
Section: $ Resultsmentioning
confidence: 99%
“…Additional trials appear to be indicated to evaluate the potential benefit of magnesium in well defined specific subsets of AMT-patients. T he outcome of patients with acute myocardial infarction (AMI) has been significantly improved during the last decade [6,19], mainly due to the extensive spread of aspirin ®, [3-blockers, and reperfusion therapy by pharmacological agents (that is thrombolytic therapy) and interventional catheterization methods [17]. However, 2 thirds of AMI-patients still do not receive lytic therapy [1,21] for a variety of reasons, and their mortality rate, especially in the elderly (> 70 years) is high, in the range of 12 to 25% [5,20,24].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the consistent reduction in the hospital mortality of AMI-patients in the last 3 decades, mainly due to extensive use of reperfusion modalities (pharmacologic-thrombolytic therapy and mechanical-catheterization-angioplasty) [6,17,19], about 70% of patients are yet not candidates for reperfusion modalities and have a high mortality rate of 12 to 25% [1, 5.20, 21, 24]. Therefore efforts have been made to find an alternative therapy for patients who cannot use reperfusion modalities, such as aspirin ®, heparin and {3-blockers and to determine the potential of adjuvant pharmacologic measures such as nitrates, angiotensin-converting enzyme inhibitors and magnesium for reducing mortality rates further.…”
Section: Discussionmentioning
confidence: 99%